Close relatives' perspective of critical illness due to COVID‐19: Keeping in touch at a distance - Anna Nordin; Åsa Engström; Ulrica Strömbäck; Päivi Juuso; Maria Andersson (Wiley, 2024)
Abstract Aim To elucidate the meaning of being a close relative of a critically ill person cared for in intensive care during the initial phase of the COVID‐19 pandemic. Design A narrative inquiry design following the COREQ guidelines. Methods Individual interviews with fifteen close relatives of patients critically ill with COVID‐19 were analysed using phenomenological hermeneutics. Results The surreal existence of not being allowed to be near was emotionally difficult. While distancing due to restrictions was challenging, physicians' phone calls served as a connection to their relatives and brought a sense of security. Keeping notes helped them remember what happened and brought order to a chaotic situation. Conclusion Close relatives feel secure when they receive regular information about their critically ill relative, not just when their condition worsens. They wish to be physically near to their critically ill person; when this is impossible, digital technology can provide support, but further accessibility developments are needed.